Intracellular Ca2 + Imbalance Critically Contributes to Paraptosis - Kim, Eunhee; Lee, Dong Min; Seo, Min Ji; Lee, Hong Jae; Choi, Kyeong Sook (Frontiers in Cell and Developmental Biology, 2021)
Paraptosis is a type of programmed cell death that is characterized by dilation of the endoplasmic reticulum (ER) and/or mitochondria. Since paraptosis is morphologically and biochemically different from apoptosis, understanding its regulatory mechanisms may provide a novel therapeutic strategy in malignant cancer cells that have proven resistant to conventional pro-apoptotic treatments. Relatively little is known about the molecular basis of paraptosis, but perturbations of cellular proteostasis and ion homeostasis appear to critically contribute to the process. Ca2+ transport has been shown to be important in the paraptosis induced by several natural products, metal complexes, and co-treatment with proteasome inhibitors and certain Ca2+-modulating agents. In particular, Ca2+-mediated communication between the ER and mitochondria plays a crucial role in paraptosis. Mitochondrial Ca2+ overload from the intracellular Ca2+-flux system located at the ER-mitochondrial axis can induce mitochondrial dilation during paraptosis, while accumulation of misfolded proteins within the ER lumen is believed to exert an osmotic force and draw water from the cytoplasm to distend the ER lumen. In this process, Ca2+ release from the ER also critically contributes to aggravating ER stress and ER dilation. This review focuses on the role of Ca2+ transport in paraptosis by summarizing the recent findings related to the actions of Ca2+-modulating paraptosis-inducing agents and discussing the potential cancer therapeutic strategies that may effectively induce paraptosis via Ca2+ signaling.